Organizational and communicative aspects in a colombian women's collective - Caicedo-Muñoz, Silvia Cristina; Clavijo Montenegro, Dayanna; Soto Vargas, Karol Dayana (Comunicación y Género [Communication and Gender], 2023)
This article aims to analyze the impact of message structure on the organizational forms of a Colombian feminist collective.The study employs the Critical Discourse Analysis and the Discursive Historical Method, utilizing the "Temporal bracketing strategy" analysis technique.The study findings support the assertion that organizational and communication components are founded on metaphors. Moreover, coherence between the textual unit of social media posts and external political and social actions is evident, constructing an organizational psychological subject.
Keywords: Communication; critical feminist analysis; discourse; legal organizations; metaphors